Norwegian Political Theatre in the 1970s: Breaking Away from the “Ibsen Tradition” - Watson, Anna (Nordic Theatre Studies, 2016)
The dominant theatre aesthetic in Norwegian theatre has been, and remains at large to be, psychological-realism and the bourgeois “living room drama”. In a Norwegian context this tradition is best represented by Henrik Ibsen’s dramas, staged at Nationaltheatret and Den Nasjonale Scene. However, throughout the 20th century there have been several attempts to break with the “Ibsen tradition”, especially among left-wing political and socially engaged theatre-makers and playwrights such as Gunvor Sartz, Olav Daalgard, and Nordahl Grieg in the 1930s, and Jens Bjørneboe and Odin Teatret in the 1960s. I argue that the clearest and most decisive break with Realism and the Aristotelian dramaturgy, in a Norwegian political theatre context, was made in the late 1970s, instigated by the independent theatre groups Perleporten Teatergruppe and Tramteatret. Their break did not only constitute an aesthetic and dramaturgical break, but also a break in organizational terms by breaking the hierarchy of the institutional theatre ‘machine’. Perleporten Teatergruppe and Tramteatret aimed at making a political, progressive theatre both in form and content. Perleporten and Tramteatret were both inspired by contemporaneous political and experimental theatre in Europe and Scandinavia as well as by the historical avant-garde experiments, and, for Tramteatret’s part, the workers' theatre movement from the 1920s and 30s in their search for a theatre that could express the social and political climate of the day. In this article, I will place Tramteatret and Perleporten Teatergruppe’s debut performances Deep Sea Thriller (1977) and Knoll og Tott (1975) within a historiographical and cultural-political context.